The general view of virtual learning environment in education sector - AlFarsi G.; Yusof A.B.M.; Rusli M.E.B.; Tawafak R.M.; Malik S.I.; Mathew R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer aided instruction; E-learning; Engineering education; 'current; (VLE) virtual learning environment; Daily lives; Development technology; Education sectors; Innovation technology; Learning frontier; Technology; Virtual learning environments; Virtual reality technology; Virtual reality